Germany’s School-Based Parent Cafés: A new Hype or a Sustainable Way to Update Home-School Policies? - Medvedev, Alexei (International Journal about Parents in Education, 2023)
The following contribution examines a socio-cultural phenomenon that has been emerging in Germany in the recent years – school-based ‘Elterncafés’ (parent cafés). Meanwhile, this term is accustomed by school development practitioners. Therefore, it still raises the question of definition. Parent cafés seem to be a promising format of cooperation between parents and schools, an attempt to attract more foreign-born parents through establishing an institutionalized but at the same time low-threshold setting that combines both Oriental and Occidental traditions of coffee houses and tea rooms. It is too early to claim the school-based parent cafés would manage to evolve a long-awaited breakthrough in home-school policies and replace out-of-date structures of school-parent communication in this country.Nevertheless, the fact is that nationwide the parent café model finds more and more advocates across all school types. One of them is the Europe School Gymnasium Hamm in Hamburg, Germany. The paper gives a vivid example how the school managed to establish its parent café in cooperation with parents, parent facilitators and BQM, a Hamburg-based think-tank. The author reflects this experience from a practitioner’s point of view and proposes some principles of a school-based parent café.